1985
DOI: 10.1007/bf00372236
|View full text |Cite
|
Sign up to set email alerts
|

Influence of paternal immunity on idiotype expression in offspring

Abstract: The immune response of the rat to group A streptococcal carbohydrate (SACHO) and an associated idiotype, Id-1, was used to examine the effect of paternal immunity on Id-1 and SACHO-specific antibody expression by the offspring. First litters, conceived before immunization of the father, had significantly higher Id-1 levels than litters conceived by the same parental pairs after hyperimmunization of the father (P greater than 0.01). Total anti-SACHO levels were not affected. The effect appeared to be independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The response of this offspring was significantly lower than the response of mice born to normal females mated only to normal mates (Gorczynski et al 1983). This type of observation has also been reported by Cooper-Willis et al (1985). In addition, Sobey and Conolly (1986) demonstrated that male domestic rabbits, mating after recovering from myxomatosis, may transmit immunity to progeny born to the female in the next 7 months, including progeny sired by other males lacking immunity.…”
Section: Possible Data In Respect Of the Existence Of Telegonysupporting
confidence: 67%
“…The response of this offspring was significantly lower than the response of mice born to normal females mated only to normal mates (Gorczynski et al 1983). This type of observation has also been reported by Cooper-Willis et al (1985). In addition, Sobey and Conolly (1986) demonstrated that male domestic rabbits, mating after recovering from myxomatosis, may transmit immunity to progeny born to the female in the next 7 months, including progeny sired by other males lacking immunity.…”
Section: Possible Data In Respect Of the Existence Of Telegonysupporting
confidence: 67%
“…Subsequent to this report, positive acquired paternal transmission reports have appeared from other independent groups (Mullbacher et al, 1983;Cooper-Willis et al, 1985) as well as later studies from my own and Dr. Gorczynski's laboratories (Steele, 1984a,b;Gorczynski et al, 1983;Steele et al, 1984). It should be noted that most of the Mullbacher et al study was conducted in the same laboratory as that of Brent et al…”
Section: Mechanism Of Directional Mutations?mentioning
confidence: 62%
“…£95% confidence interval 5.7-9.2, range 5.5-9.5. (7,8,(16)(17)(18)(19), STZ-D, possibly involving an active autoimmune disease, specific for (3-cells, might itself favor the transmission of acquired paternal diabetic effects. In addition, the decision to use this type of diabetic male in the breeding program was reinforced by the observation of Like and Rossini (13) that the insulitis caused by multiple subdiabetogenic doses of STZ is associated with the induction of endogenous type C viruses in p-cells (not observed after delivery of a single high sublethal dose of STZ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of this obviously complex paternal transmission phenomenon is unknown. Whether the process is related to acquired antigen-induced paternal-inheritance effects documented for the immune system is unknown and will only be clarified by further work (7,8,(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%